Research on the antibacterial mechanism of medical nanosilver latex composite materials - Meng, Zhuang; Fan, Bin; Yan, Pengyu; Liu, Chun (Frontiers in Materials, 2024)
Objective: This study investigates the antibacterial mechanisms of medical nanosilver latex materials by conducting antibacterial experiments on nanosilver latex, observing the morphological changes in Escherichia coli after co-cultivation with nanosilver, and detecting variations in nitric oxide, malondialdehyde, protein, and DNA fragment content. The aim is to provide a theoretical foundation for the application of antibacterial materials in medical settings.Methods: To prepare the composite latex film, nanosilver was combined with natural latex. The antibacterial efficacy of nanosilver latex were assessed using co-cultivation and colony counting methods. Electron microscopy facilitated the observation of Escherichia coli post cocultivation with nanosilver, and subsequent changes in nitric oxide, malondialdehyde, protein, and DNA fragment content were measured.Results: The composite film of nanosilver latex demonstrated antibacterial properties, which were proportional to its concentration and inversely proportional to the particle size. Exposure to nanosilver resulted in bacterial cell membranes, leading to increased levels of nitric oxide, malondialdehyde, protein, and DNA content within bacteria.Conclusion: Nanosilver particles, especially those of 10 nm, were found to be most effective in antibacterial activity. The antibacterial effects were primarily due to the disruption of bacterial cell membranes and walls, altering intra and extracellular osmotic pressure, inducing lipid peroxidation of bacterial cell membranes, triggering of oxidative stress, and damage to DNA.